Convective heat transfer in microchannels with varying flow cross-section - Cheng, Kai Xian (Nanyang Technological University, 2020)
The microchannel heat sinks offer superior heat transfer capabilities. In the past three decades, these microchannels have been studied extensively in terms of design and implementation, fundamental understanding of heat transfer and fluid flow, as well as the enhancement techniques in heat transfer. These thermally-efficient channels have found applications in the industries where space and thermal performance are the key drivers. However, cost-effective manufacturing is a hurdle for the proliferation of microscale heat transfer in the wider commercial applications.